Human umbilical cord tissue stem cells and neuronal lineages in an injectable caffeic acid–bioconjugated gelatin hydrogel for transplantation. Issue 3 (24th August 2018) - Subbarayan, Rajasekaran; Girija, Dinesh Murugan; Rao, Suresh Ranga
Abstract : Present‐day scaffolds are useful in cell therapy to a reasonable extent, but in pursuit of improvising the scaffold to improve the outcome, we tested a new injectable caffeic acid–bioconjugated gelatin hydrogel scaffold (CBGH; with tunable stiffness −10%). Two‐dimensional (2D) form of human umbilical cord tissue‐derived mesenchymal stem cells (HUCMSCs) culture performed based on our previously reported methods and characterized by using multipotent and pluripotent analysis. In addition, neurogenesis was induced in the presence of retinoic acid or neural growth factor or epidermal growth factor categorized by neuronal markers. The viability, proliferation rate, and vascular endothelial growth factor expression of HUCMSCs increased significantly in the CBGH scaffold. In addition, there was an increase in CD90 and TRA‐1‐81 phenotypic expressions and SOX‐2, MAP‐2, TAU, NeuN, and NF, which confirmed the neurogenesis of encapsulated HUCMSCs. Topographical elucidation by scanning electron microscopy data showed that the HUCMSCs proliferated and migrated inside the construct. Hematoxylin and eosin staining demonstrated a more viable structural pattern and cresyl violet staining showed the Nissl synthesis, confirming the presence of functional neurons in the encapsulated form. The molecular‐level analysis further substantiated that HUCMSCs cultured in CBGH expressed significantly greater upregulation of stemness, neuronal genes, and protein expression compared with the adherent culture. Correspondingly, this is the first time that we have measured the fluorescence intensity variation of the HUCMSCs‐stained cell segmentation process using customized MATLAB code execution to reduce the background noise and autofluorescence. We conclude that this novel CBGH scaffold increases the viability, proliferation, stemness, and also neuronal transdifferentiation of HUCMSCs in a three‐dimensional culture than the 2D plastic adherent culture. Abstract : Developed a novel caffeic acid based gelatin hydrogel construct for umbilical cord‐derived MSCs and its neuronal linage analysis for transplantation purpose.